2012
DOI: 10.1371/journal.pone.0051235
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Behaviors Modeling Aspects of Schizophrenia in Csmd1 Mutant Mice

Abstract: Schizophrenia is a debilitating psychotic disorder that affects up to 1.5% of the population worldwide. Two recent studies in humans identified genome-wide significant associations between schizophrenia and single-nucleotide polymorphisms (SNPs) in an intron of CSMD1. The effect of deleting CSMD1 on mouse behavior is unknown. The present study utilized mice with a mutant Csmd1 allele in which the first exon had been ablated (KO mice). All Csmd1 transcripts that included the first exon were absent in the brains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…In the present study we also identified a cis-eQTL 319 for Csmd1 in HIP (Supplemental Fig.S7). Finally, we obtained Csmd1 mutant mice (Distler et al 2012) 320 and found that they also showed altered locomotor activity (Fig.5E). Thus, we have demonstrated 321 replication both by performing an independent GWAS and by performing an experimental manipulation 322 that recapitulates the phenotype.…”
Section: Cc-by-nc 40 International License Peer-reviewed) Is the Autmentioning
confidence: 93%
See 1 more Smart Citation
“…In the present study we also identified a cis-eQTL 319 for Csmd1 in HIP (Supplemental Fig.S7). Finally, we obtained Csmd1 mutant mice (Distler et al 2012) 320 and found that they also showed altered locomotor activity (Fig.5E). Thus, we have demonstrated 321 replication both by performing an independent GWAS and by performing an experimental manipulation 322 that recapitulates the phenotype.…”
Section: Cc-by-nc 40 International License Peer-reviewed) Is the Autmentioning
confidence: 93%
“…Its four major transcripts, termed Csmd1-1 to Csmd1-4, are expressed in the 512 central nervous system (Distler et al 2012). Distler et al (2012) demonstrated that Csmd1 homozygous 513 mutant mice express <30% of wild-type Csmd1 levels in the brain, and heterozygous mice show a 54% 514 reduction in Csmd1 expression. Residual expression of Csmd1 in homozygous mutant mice is derived 515 from Csmd1-4, the only transcript that does not include the first exon.…”
Section: Csmd1 Tm1lexmentioning
confidence: 99%
“…15,16 For example, the sweet-preference test in animals measures preference for a sweet vs a nonsweet solution, thought to reflect anhedonia in schizophrenia. Despite the large number of studies investigating this phenomenon in rodents claiming this relation, [17][18][19][20] when patients with schizophrenia were finally tested, they exhibited normal preference for juice (ie, sweet solution) despite their high negative symptom scores. 21 Considering the difficulty of linking interview-based rating scales to laboratory behavioral tasks in experimental animals (figure 1), "the present review describes procedures that quantify motivation and reward valuation in rodents in a similar parametric fashion to tests that can be conducted in humans and briefly describes what is known of the neuromechanisms underlying these behaviors."…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, mice and rats are commonly used animal models to study behavior in the laboratory for many reasons. The mouse is currently the mammalian model of choice for studying gene–behavior interactions because of its close genetic similarities to humans, and the ease with which its genome can be manipulated and analyzed (Distler et al, ; Ortiz et al, ). Conversely, rats are more social, display sophisticated sexual behaviors, strong spatial navigation and learning, and are favored in studying brain–behavior interactions (Berridge, ; Crawley and Paylor, ; Frick et al, ; Kalueff and Tuohimaa, ; Whishaw and Tomie, ).…”
Section: Introductionmentioning
confidence: 99%